THE PRELIMINARY STUDY OF ANTIOXIDANT ACTIVITY FROM XYLO-OLIGOSACCHARIDE OF CORNCOB (ZEA MAYS) HYDROLYSIS PRODUCT WITH ENDO-β-XYLANASE ENZYME - Yamani, Laura Navika; Kristanti, Alfinda Novi; Puspaningsih, Ni Nyoman (Indonesian Journal of Tropical and Infectious Disease, 2012)
Xylo-oligosaccharide derived from corncob hemicellulose has been reported to possess antioxidant activity. In order to assess the effective scavenging of xylo-oligosaccharide, we conducted in vitro studies based on self-made xylo-oligosaccharide with DPPH (2,2diphenyl-1-picrilhydrazil) method. Xylo-oligosaccharide was prepared with enzymatic hydrolysis. The enzyme used for hemicellulose hydrolysis was endo-β-xylanase enzyme from PC-01 isolated bactrerium. PC-01 isolated bacterium used in this study was Pacet hot spring which was isolated from East Java. Endo-β-xylanase enzyme is an extracelluler enzyme. There was about 0.199 U/mL after purification and dialysis process. Hydrolisis product of hemicellulose A and B from corncob were analyzed with TLC (Thin Layer Chromatography) and HPLC (High Performance Liquid Chromatography). This analysis showed that hydrolysis product of hemicellulose B had a lot of xylo-oligosaccharide hydrolysis product of hemicellulose than Xylo-oligosaccharide hydrolysis product of hemicelluloses A. Xylo-olygosaccharide was analyzed as on antioxidant activity. Xylo-oligosaccharide hydrolysis product ofhemicellulose B (IC = 48.96) has higher antioxidant activity than Xylo-oligosaccharide hydrolysis product of hemicellulose A (IC 50 50 = 92.302). The toxicity of xylo-oligosaccharide can be calculated by the value of LC 50 (Lethality concentration). LC of xylooligosaccharide derived from corncob hemicellulose was 400 ppm so that xylo-oligosaccharide has anti tumor activity because xylooligosaccharide has LC 50 < 1000 ppm.